(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background: Sperm viability of human spermatozoa in Assisted Reproductive Technique(ART) is one of the major concerns as many changes occur in sperm cells as a result of Cryopreservation, including membrane abnormalities and cell death namely apoptosis and Necrosis. Aim: The prime motive of this study is to identify the best washing method for Oligoasthenospermic patients who undergo ART by analyzing early apoptosis, late apoptosis and necrosis after cryopreservation of sperm for a period of three months. Study Setting and Design: Three methods of sperm washing viz. Density Gradient, Swim-up and Magnetic Activated Cell Sorting methods were used for comparative analysis for which semen samples were obtained from 30 Oligoasthenozoospermia patients with progressive motility of less than 32%, who underwent ART procedure at Sumathi Fertility Centre, Madurai between June-October 2021. Informed consent was obtained from all men prior to the study. This research was approved by the institutional review board of Bharath University, Chennai.SBDCH/IEC/02/2017/09.Materials and Methods: Briefly, the semen sample was subjected to the three washing methods. After washing, the samples were cryopreserved in liquid nitrogen for a period of 3 months. After 3 months Apoptosis, Necrosis and viability were assessed by using EtBr and Acridine orange stain. Statistical Analysis: IBM SPPS version 2.0 was deployed to measure the viability of semen using the three washing method. Results: The swim-up method had higher early and late apoptosis seen in it and a Yellowish green colour showed early apoptosis and an Orange colour was seen with respect to late apoptosis. The viable cells were seen more in the Density gradient method whereas the Magnetic Cells sorting method showed increased levels of Necrosis. The density gradient method more viable able cells compared to swim-up and magnetic activated and cell sorting methods. Early and late apoptosis is more seen in the Swim-up method unsuitable for ICSI and IVF. The magnetic method shows high necrosis in semen processing and is unsuitable for the ICSI method.